(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
The continued use of fossil fuels will increase the concentration of carbon dioxide (CO2) in the atmosphere. Ocean acidification occurs due to CO2 in the atmosphere diffusing into the oceans. The oceans are able to absorb CO2 in the atmosphere as much as 35 % more which causes a decrease in ocean pH. Seagrass Cymodocea rotundata is a type of seagrass that can be found growing in tropical waters. This situation raises concerns about the possible impact on the growth of seagrass C. rotundata. This study aims to analyze the content of nitrate, phosphate and potassium and the growth of seagrass C. rotundata which includes the growth of leaves, rhizomes and roots of C. rotundata against differences in pH. The study used an experimental method with a completely randomized design using a random table. A total of 15 jars with a diameter of 20 cm and a height of 25 cm were used with 3 treatments, each treatment was repeated 5 times. The results of the linear regression test showed that pH had an effect on nitrate concentrations, and had a strong effect on phosphate and potassium concentrations. The highest growth rate of C. rotundata seagrass leaves in the control ranged from 0.50–1.29 mm/day while the lowest at low pH ranged from 0.07–0.73 mm/day. The growth rate of seagrass rhizomes horizontally and vertically was highest at low pH while the lowest was at control pH. The highest growth rate of seagrass roots at low pH ranged from 0.20–0.90 mm/day. while the lowest was in the control ranged from 0.13–0.43 mm/day. pH also affects the growth rate of leaves, rhizomes and seagrass roots of C. rotundata. The lower the pH, the lower the leaf growth rate, in contrast to rhizomes and roots, the lower the pH, the higher the growth rate.